Allelic diversity in the CAD2 and LIM1 lignin biosynthetic genes of Eucalyptus grandis Hill ex Maiden and E. smithii R.T. Baker - Myburg, Alexander Andrew (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2009.